2020
DOI: 10.1038/s41467-020-18015-5
|View full text |Cite
|
Sign up to set email alerts
|

Surface chelation of cesium halide perovskite by dithiocarbamate for efficient and stable solar cells

Abstract: Surface engineering has been shown critical for the success of perovskite solar cells by passivating the surface enriched defects and mobile species. The discovery of surface modulators with superior interaction strength to perovskite is of paramount importance since they can retain reliable passivation under various environments. Here, we report a chelation strategy for surface engineering of CsPbI 2 Br perovskite, in which dithiocarbamate molecules can be coordinate to surface Pb sites via strong bidentate c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(106 citation statements)
references
References 54 publications
5
93
0
Order By: Relevance
“…The calculated results indicated that Cs and Pb both have considerable binding energy with the Crown ether (−2.79 and −1.97 eV, respectively, Figure S15, Supporting Information), demonstrating that the interaction could effectively stabilize the surface avoiding the moisture attacking. [ 43 ] The relative higher binding energy ( ∆ = 0.82 eV) for Cs with Crown than Pb also indicates the stronger interaction between Crown and Cs + ions, which was consistent with the 1 H NMR and XPS measurements. The above results unraveled that the strong binding of Crown with Cs + or Pb 2+ surface ions indeed could protect the FACsPbI 3 films from the moisture induced degradation for the more stable device performance.…”
Section: Resultssupporting
confidence: 79%
“…The calculated results indicated that Cs and Pb both have considerable binding energy with the Crown ether (−2.79 and −1.97 eV, respectively, Figure S15, Supporting Information), demonstrating that the interaction could effectively stabilize the surface avoiding the moisture attacking. [ 43 ] The relative higher binding energy ( ∆ = 0.82 eV) for Cs with Crown than Pb also indicates the stronger interaction between Crown and Cs + ions, which was consistent with the 1 H NMR and XPS measurements. The above results unraveled that the strong binding of Crown with Cs + or Pb 2+ surface ions indeed could protect the FACsPbI 3 films from the moisture induced degradation for the more stable device performance.…”
Section: Resultssupporting
confidence: 79%
“…To date, champion PCEs of 17.03% and 15.92% have been achieved for n–i–p‐type (normal) and p–i–n (inverted)‐type PeSCs, respectively, both based on CsPbI 2 Br. [ 12–18 ] Nevertheless, such PCE values are still lower than those of hybrid PeSCs. Further improvement is highly demanded for all‐inorganic PeSCs.…”
Section: Introductionmentioning
confidence: 94%
“…[17,41,42] Strategies include precursor engineering, surface passivation/engineering, 2D/3D interface engineering, and architecture engineering. [15,19,21,[43][44][45][46][47][48][49] It is worth mentioning that most of the highest-efficiency single junction Cs-based all-inorganic PSCs are realized with the n-i-p structure, while there are only a few works describing high-efficiency p-i-n all-inorganic PSCs. [50,51] This is mainly due to concomitant challenges in material and interface optimization in p-i-n configuration, [51,52] leading to lower open circuit Figure 3.…”
Section: Paths Toward High Efficiencymentioning
confidence: 99%
“…Several strategies, such as anion and B-site doping, surface passivation, architecture engineering, and crystal-growth engineering, have been applied to increase the resistance of the material toward moisture, heat, and light exposure. [17,46,[58][59][60][61] Regarding the B side doping, in 2020, Yao et al reported a doping strategy to improve both the efficiency and the stability of the CsPbI 3 -based device by adding Mn 2+ ions into Figure 5. A) Schematic mechanism for DMAI additive induced black phase CsPbI 3 formation.…”
Section: Paths Toward Improved Stabilitymentioning
confidence: 99%